Pengaruh Keterlibatan Siswa dalam Teaching Factory, Motivasi Belajar dan Praktik Kerja Industri terhadap Kesiapan Bekerja Siswa Sekolah Menengah Kejuruan - Rahmat Al Hidayat; Muhammad Sayuti; Budi Santosa (Jurnal Syntax Admiration, 2024)
This study aims to: (1) analyze the effect of the teaching factory learning process on the job readiness of SMK Muhammadiyah Majenang students; (2) analyze the effect of learning motivation on the job readiness of SMK Muhammadiyah Majenang students. This study used quantitative methods. Hypothesis test using multiple liner regression analysis processed using SPSS program with data tabulation stages, classical assumption test (multicollinearity, heteroscedasticity, normal P-P plot), model feasibility test (simultaneous significance test F test, significance test of individual parameters t test, determination coefficient test), and interpretation of linear regression models. The results of the study are as follows: (1) student involvement in Teaching Factory Learning has a significant effect on Work Readiness. (2) Student learning motivation has a significant effect on job readiness. (3) Industrial work practices have a significant effect on students' job readiness. (4) Teaching Factory learning, learning motivation and industrial work practices have a significant effect on student job readiness. The factors forming teaching factory learning are curriculum, content standards, process standards, facilities, infrastructure, human resources, personnel management, operational management, and partnerships. Factors forming learning motivation, instrumental, social, achievement and intrinsic motivation. While the factors forming industrial work practices are training management skills, solving problems, applying conceptual domains, discipline, orderly industrial culture, responsibility, occupational safety and health.